If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7-1(x-5)=6-2x
We move all terms to the left:
-7-1(x-5)-(6-2x)=0
We add all the numbers together, and all the variables
-1(x-5)-(-2x+6)-7=0
We get rid of parentheses
-1(x-5)+2x-6-7=0
We add all the numbers together, and all the variables
2x-1(x-5)-13=0
We move all terms containing x to the left, all other terms to the right
2x-1(x-5)=13
| 12x+28/12=4+2x/25 | | 9(m+9)=63 | | 6(4+5x)=2x-4 | | 0.2=x/0.8 | | 9(m+9)=3 | | 6j-6j+3j-2j+J=10 | | -7(-2+7x)=-38+3x | | -5(x+2)=-10(x+1/5) | | -x-2=10-7x | | 10-4x=5x-26 | | -5x-16=-2(1+4x)+1 | | 20m-9m-5m+m=14 | | -6x+18=-2(4x-6)+3x | | -9-x=-3x+11 | | 7x+2=27+2x | | -6x+40=-2(5x-6) | | 4j-2j=6 | | d/4+17=19 | | 0.625-0.75=2x+4x | | 234=p*2/3*1/2 | | 3/4x+3=5/3 | | 6y+4+11y=-16-4 | | y=-3(8)+5 | | 11=2c+-9 | | 15-2x+31=0 | | 1-10=-22+4x | | -4(1-6x)=-148 | | y=-3(4)+5 | | -5x+2=-70+x | | -129=-3(1-6x) | | C+5c-2c=4 | | 3+7x=5x+25 |